In Memoriam - CPH 62(1) (Czasopismo Prawno-Historyczne, 2010)
Kazimierz Orzechowski 1923-2009 (Marian J. Ptak) ... 499 Mario Talamanca 1928-2009 (Witold Wołodkiewicz) ... 504 André Gouron 1931-2009 (Wacław Uruszczak) ... 506